ACTIVE LIFESTYLE OF STUDANTS: AN EDUCATIONAL INTERVENTION (Fiep Bulletin - online, 2014)
In recent years, studies in the area of public health stress style and physical activity as essential components of lifestyle. Physical Activity has gained attention for its contribution to the quality of lifestyle and its relevant role in the prevention of diseases and pathologies. Therefore, this study aimed at implementing and evaluating an educational intervention to promote this active lifestyle with high school students. It was an experimental investigation with students between 14 and 19 years of age, in two public schools of Fortaleza (CE). Students were divided into three groups of intervention group and three groups in the control group. The questionnaire: Lifestyles of Students was used as a research tool, in which we applied the chi -square in the three stages of the assessment (pretest, post-test and re-test). We considered as statistically significant only those results with p-value less than or equal to 5% (p ? 0.05). Analyses were performed using the SPSS 15.0 version for Windows. Pretest: the number of boys in the control group in the category "very active" was the largest.Post-test: the number of students in general and girls in the intervention group was higher in the "active" and "very active" categories; Re-test: students, in general, in the intervention group remained in the "very active" category. We conclude that the intervention was effective in promoting and maintaining an active lifestyle, i.e., to increase the levels of physical activity for all students in the short and long term, especially among girls.
Keywords: Active Lifestyle; Students; Intervention.